The effect of diabetes mellitus on chronic rhinosinusitis and sinus surgery outcome. Issue 4 (10th January 2014) - Zhang, Zi; Adappa, Nithin D.; Lautenbach, Ebbing; Chiu, Alexander G.; Doghramji, Laurel; Howland, Timothy J.; Cohen, Noam A.; Palmer, James N.
<x xml:space="preserve">Abstract</x> Background Patients with diabetes mellitus (DM) are known to be prone to infection. However, the association between diabetes and chronic rhinosinusitis (CRS) has not been well studied. We sought to determine the effects of DM on CRS culture results and quality of life (QOL) after functional endoscopic sinus surgery (FESS). Methods We conducted a retrospective cohort study. Adult CRS patients undergoing FESS were recruited from October 1, 2007 to December 31, 2011. Patient demographics, comorbidities, medication use, and Lund‐Mackay CT scores were collected prior to FESS. Intraoperative culture was obtained. Preoperative and 1‐month, 3‐month, and 6‐month postoperative QOL was measured by scores on the 22‐item Sinonasal Outcome Test (SNOT‐22). A mixed effects model was performed for analysis. Results Among the 376 CRS patients included, 19 patients (5.05%) had DM. Compared to non‐DM patients, DM patients were significantly more likely to have Pseudomonas aeruginosa (26.32% vs 7.56%; p = 0.004) and Gram‐negative rods (26.32% vs 8.96%; p = 0.013), but there was no significant difference in the prevalence of Staphylococcus aureus; DM patients were also significantly more likely to have nasal polyps and gastroesophageal reflux disease. Additionally, DM patients had significantly less improvement of postoperative SNOT‐22 scores from baseline to 6‐month follow‐up than non‐DM patients (adjusted mean = 11.14, 95% CI (0.14, 22.15), p = 0.047) after adjusting for all the other risk factors for CRS. Conclusion DM patients may be prone to Gram‐negative bacterial sinus infections, and have significantly worse short‐term postoperative QOL. Special postoperative care may need to be considered in CRS patients with DM.